Dal captivity tale al prison movie: immaginari di lunga durata nella produzione seriale americana - Tarzia, Fabio (Mediascapes journal, 2016)
The paper that is proposed here tries to observe and analyze a real transmedia narrative modus, of obvious serial imprinting and at the same time long-lasting. It is the narrative form typically American that begins at the seventeenth with the captivity tale and cames until today with the prison movie. The analysis will initially be addressed to demonstrate the specificity of the american mass production than in Europe. It will be taken to highlight the continuity of functions between seemingly different genres (captivity and prison) and then groped to provide an explanation. Finally, we will observe the contemporary situation, trying to bring out the possible functional transformation with regard to different media environments through which the narrative takes shape today.